Thiazolidin-5-imine formation as a catalyst-free bioorthogonal reaction for protein and live cell labeling - Bi, Xiaobao (2021)
A previously undescribed reaction involving the formation of a thiazolidin-5-imine linkage was developed for bioconjugation. Being highly specific and operating in aqueous media, this simple condensation reaction is used to chemoselectively label peptides, proteins, and living cells under physiological conditions without the need to use toxic catalysts or reducing reagents.